OPTIMALISASI TEMPERATUR PEMANASAN CETAKAN PERMANEN (300OC, 350OC, 400OC) TERHADAP SIFAT MEKANIK PADUAN ALUMINIUM-MAGNESIUM (SERI 5XXX) - Widodo, Basuki (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
Aluminium is a light metal which has a very good physical and mechanical properties and it easy to be formed. Casting of aluminium posses some advantages high conductivity and low melting point, enables applied permanent mold too. Material that is used to make mold is from special steel, and when casting process, after aluminium-mag-nesium alloy melting will be poured in mold hence after the permanent mold heated in va-rious temperature which has been determined that is, 300 oC, 350 oC and 400 oC. Heat-ing of mold at this research meant to know how far the influence is happened to mechani-cal properties from Aluminium-Magnesium alloy (series 5xxx) especially tensile strength, hardness and transformation of microstructure. From result of research which to be got best tensile strength value to draw alloy Aluminium-Magnesium (Al-Mg) at 350 oC tem-perature equal to 11,11 kg/mm2 and highest hardness at 350 oC temperature equal to 101,64 HB (Hardness Brinnel) while microstructure that is very homogen also there is at temperature 350 oC.